Newly-formed sea ice distinction near the oil platform Prirazlomnaya in the Pechora Sea using polarimetric Radarsat-2 SAR observations - Ivonin, Dmitry; Ivanov, Andrey; Johansson, Malin; Brekke, Camilla (VDE Verlag, 2021)
Source at https://www.vde-verlag.de/proceedings-de/455457112.html . A polarimetric approach developed to discriminate oil slicks and look-alikes was used to study the polarimetric properties of newly-formed ice (NFI) observed near the Prirazlomnaya oil platform. This approach is based on the multipolarization parameter called Resonant to Non-resonant signal Damping (RND), which is related to the ratio between the ice damping and the short wind waves and wave breakings. Fully-polarimetric Radarsat-2 images containing NFI were analyzed. The RND parameter indicates that in many cases the damping of the resonant and non-resonant electromagnetic signals in NFI is significantly different from oil slicks and that the RND parameter can distinguish them.